Transferência de conhecimento e mensuração de inovação em micro e pequenas empresas da construção civil das cidades de Toledo, Cascavel, Medianeira e Foz do Iguaçu - Souza, Kássia Esteves de (2020)
The objective of this study is to verify the process, the degree and the importance of the download of knowledge in the generation of innovation of civil construction builders, such as micro and small companies in the cities of Toledo, Cascavel, Medianeira and Foz do Iguaçu during the interval of 2017 to 2019. To achieve this goal, a study was carried out with 16 builders through the Local Innovation Agents Program (ALI) in partnership with the Brazilian Micro and Small Business Support Service (SEBRAE). To measure the level of innovation applied to the Innovation Radar to examine 13 dimensions, it is also possible to perform the Wilcoxon Test calculated to check whether there is an eventual knowledge transfer and analysis of individual graphics during the periods from 2017 to 2019 of the builders and tests. The results found clarify that there is an innovative behavior. As builders, they demonstrated that there was more frequency of innovation and knowledge transfer. The transfer of knowledge positively interfered in the innovation indexes statistically of the 16 construction companies analyzed in the period of 3 years. It is visible how for MEPs to obtain and put into practice the insertion of innovative activities or methods to increase the innovation index. Knowledge transfer has proven to be efficient in increasing economic development and builder development. In this way, demonstrate the SEBRAE ALI program achieved the objectives established as studied builders.